The Effectiveness of Teachers’ Performance of Islamic Junior High School in Islamic Boarding School Langkat District, Indonesia - Nasution, Wahyudin Nur (Jurnal Ilmiah Peuradeun, 2018)
This study aims to determine the relationship between emotional intelligence, self-concept and the performance effectiveness of Islamic Junior High School teachers in Islamic Boarding School, Langkat District, North Sumatra, Indonesia. This research used survey method with correlation technique. The sample in this study amounted to 32 teachers and the research data were collected by using questionnaires. All data were analyzed by using simple and multiple regression and correlation statistic. The results of this study revealed that: (1) there is a positive relationship between emotional intelligence and the effectiveness of teachers’ performance, (2) there is a positive relationship between self-concept and the effectiveness of teachers’ performance, and (3) there is a positive relationship between emotional intelligence, self-concept and the effectiveness of teachers’ performance.